Effect of folA gene in human breast milk-derived Limosilactobacillus reuteri on its folate biosynthesis - Jiang, Yu; Li, Xianping; Zhang, Wei; Ji, Yadong; Yang, Kai; Liu, Lu; Zhang, Minghui; Qiao, Weicang; Zhao, Junying; Du, Mengjing; Fan, Xiaofei; Dang, Xingfen; et al. (Frontiers in Microbiology, 2024)
Introduction Folate supplementation is crucial for the human body, and the chemically synthesized folic acid might have undesirable side effects. The use of molecular breeding methods to modify the genes related to the biosynthesis of folate by probiotics to increase folate production is currently a focus of research. Methods In this study, the folate-producing strain of Limosilactobacillus reuteri B1-28 was isolated from human breast milk, and the difference between B1-28 and folA gene deletion strain ΔFolA was investigated by phenotyping, in vitro probiotic evaluation, metabolism and transcriptome analysis. Results The results showed that the folate producted by the ΔFolA was 2–3 folds that of the B1-28. Scanning electron microscope showed that ΔFolA had rougher surface, and the acid-producing capacity (p = 0.0008) and adhesion properties (p = 0.0096) were significantly enhanced than B1-28. Transcriptomic analysis revealed that differentially expressed genes were mainly involved in three pathways, among which the biosynthesis of ribosome and aminoacyl-tRNA occurred in the key metabolic pathways. Metabolomics analysis showed that folA affected 5 metabolic pathways, involving 89 different metabolites. Discussion In conclusion, the editing of a key gene of folA in folate biosynthesis pathway provides a feasible pathway to improve folate biosynthesis in breast milk-derived probiotics.